The Reflection of Regency Gentleman in Pride and Prejudice and Emma by Jane Austen - Andi Febriana Tamrin (Universitas Cokroaminoto Palopo, 2018)
This study is aimed to present the nature of gentleman in the Regency era as reflected in the selected novels of Jane Austen, entitled Pride and Prejudice and Emma. The men who are categorized as gentleman are shifted over the years. In the time before Industrial Revolution, the term “gentleman” belongs to nobility class, gentry or to men who did not use their own hands to work. However, after the Victorian era, the “gentleman” covers several terms. These are the army, clergy, and even for the merchants. The social class and wealth are the prominent factors that cause the changing of this pattern. Nevertheless, Austen’s concept of gentleman in her two novels is referred mostly by the virtue and behavior.